2010
DOI: 10.1519/jsc.0b013e3181da786f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Attributes of Human Skeletal Muscle at Rest and After Unaccustomed Exercise: An Age Comparison

Abstract: The current study examined muscle DNA and protein concentrations ([ ]) and the [RNA] (assumed to represent translational capacity), [RNA]:[DNA] (assumed to represent transcriptional efficiency) and [protein]:[RNA] (assumed to represent translational efficiency) in younger vs. older participants during a resting state. Further, changes in muscle [DNA], translational capacity, and transcriptional efficiency were analyzed 24 hours after an unaccustomed resistance exercise bout. Younger (20.9 +/- 0.5 years, 84.0 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
(35 reference statements)
2
8
1
1
Order By: Relevance
“…Our observations of reduced ribosome content and biogen- esis during hyperammonemia-induced muscle loss are consistent with those reported for disuse-related muscle atrophy, where lower skeletal muscle RNA content was noted in rats during hindlimb immobilization and spinal cord injury (66,67) or in humans during inactivity (68). Importantly, this phenomenon is different from aging-related sarcopenia and sciatic denervation-induced atrophy, where the skeletal muscle total RNA concentration is not decreased (31,65). Also, our data show that ribosomal alterations in muscle atrophy are not necessarily the reverse of hypertrophy, because the changes in hypertrophy are believed to be due to translational rather than transcriptional perturbations (27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observations of reduced ribosome content and biogen- esis during hyperammonemia-induced muscle loss are consistent with those reported for disuse-related muscle atrophy, where lower skeletal muscle RNA content was noted in rats during hindlimb immobilization and spinal cord injury (66,67) or in humans during inactivity (68). Importantly, this phenomenon is different from aging-related sarcopenia and sciatic denervation-induced atrophy, where the skeletal muscle total RNA concentration is not decreased (31,65). Also, our data show that ribosomal alterations in muscle atrophy are not necessarily the reverse of hypertrophy, because the changes in hypertrophy are believed to be due to translational rather than transcriptional perturbations (27).…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in ribosomal biogenesis in this model was shown to be due to an increase in proteasomal activity, suggesting translational deficits rather than global transcriptional mechanisms as mediators of aging-related muscle loss (28). In contrast, others have reported unaltered or even increased skeletal muscle ribosomal biogenesis with aging (29)(30)(31). These conflicting observations may be indicative of a compensatory increase in ribosome biogenesis during muscle atrophy or a context-dependent response.…”
mentioning
confidence: 71%
“…While this observation contrasts prior literature reporting that skeletal muscle ribosome density is similar in younger vs. older humans (Roberts et al, 2010; Stec et al, 2015) or is greater in older rats (Haddad and Adams, 2006), this finding may be due to our examination of the plantaris muscle vs. the examination of vastus lateralis tissue in humans or gastrocnemius muscles in rats in the aforementioned studies; both which contain a heterogeneous mixture of type I and II fibers. Notably, soleus muscle total RNA levels did not differ between age groups which suggests that slow-twitch fiber ribosome density does not decrease with aging in Fisher rats.…”
Section: Discussioncontrasting
confidence: 99%
“…It was also suggested that tissue damage, a stimulus for repair and tissue hypertrophy resulting from muscle‐damaging exercise, may be sufficient to contribute to the increased total energy during recovery (Burleson et al., ). Although the findings of the above investigations are based on young individuals, they could be applied in the present study considering the observation that the intrinsic regenerative capacity of skeletal muscle and satellite cells is not impaired with age (Conboy et al., ; Roberts et al., ).…”
Section: Discussionmentioning
confidence: 99%